Bio-desulfurization of biogas using acidic biotrickling filter with dissolved oxygen in step feed recirculation. (March 2015) - Chaiprapat, Sumate; Charnnok, Boonya; Kantachote, Duangporn; Sung, Shihwu
Graphical abstract: Highlights: Triple stage biotrickling filter was superior to single stage biotrickling filter. H2 S removal efficiency was enhanced by step feeding O2 rich liquid recirculation. 1st order removal rate coefficient of T-BTF was 47% higher than S-BTF. Larger liquid recirculation shifted O2 /H2 S balance system to complete oxidation. Sulfuric acid production improved with an increasing liquid recirculation velocity. Abstract: Triple stage and single stage biotrickling filters (T-BTF and S-BTF) were operated with oxygenated liquid recirculation to enhance bio-desulfurization of biogas. Empty bed retention time ( EBRT 100–180 s) and liquid recirculation velocity ( q 2.4–7.1 m/h) were applied. H2 S removal and sulfuric acid recovery increased with higher EBRT and q . But the highest q at 7.1 m/h induced large amount of liquid through the media, causing a reduction in bed porosity in S-BTF and H2 S removal. Equivalent performance of S-BTF and T-BTF was obtained under the lowest loading of 165 gH2 S/m 3 /h. In the subsequent continuous operation test, it was found that T-BTF could maintain higher H2 S elimination capacity and removal efficiency at 175.6 ± 41.6 gH2 S/m 3 /h and 89.0 ± 6.8% versus S-BTF at 159.9 ± 42.8 gH2 S/m 3 /h and 80.1 ± 10.2%, respectively. Finally, the relationship between outlet concentration and bed height was modeled. Step feeding of oxygenated liquid recirculation in multiple stages clearly demonstrated an advantage for sulfide oxidation.